A Robotic Guide for Blind People. Part 1. A Multi-National Survey of the Attitudes, Requirements and Preferences of Potential End-Users - Marion A. Hersh; Michael A. Johnson (Applied Bionics and Biomechanics)
This paper reports the results of a multi-national survey in several different countries on the attitudes, requirements and preferences of blind and visually impaired people for a robotic guide. The survey is introduced by a brief overview of existing work on robotic travel aids and other mobile robotic devices. The questionnaire comprises three sections on personal information about respondents, existing use of mobility and navigation devices and the functions and other features of a robotic guide. The survey found that respondents were very interested in the robotic guide having a number of different functions and being useful in a wide range of circumstances. They considered the robot's appearance to be very important but did not like any of the proposed designs. From their comments, respondents wanted the robot to be discreet and inconspicuous, small, light weight and portable, easy to use, robust to damage, require minimal maintenance, have a long life and a long battery life.